Analysis Mapping Application Of Geographic Information System Hospital - Amelia D; Sukoco A (Bandar Lampung University (UBL), 2017)
The development of increasingly rapid technological changes that make the rise. No wonder if all of the current facility has much mapped into a digital form that is easier for everyone to search for it.This is the main attraction in the development of location-based services technology. The hospital is a professional health care institutions whose services are provided by doctors, nurses,and other health professionals. Along with needed her more in the hospital, then every community is expected to know the locations of the hospital closest to the place of residence to anticipate things thatare not desirable. It takes a Geographic Information System application that can help people to find out where the locations of hospitals that will go.In this study, the authors wanted to learn how to build the information system applications, so that the writer can know clearly about the design of information technology, and can be implemented in future studies.